Importance of muscles for structure and function of oral cavity organs - Śmiech-Słomkowska, Grażyna; Peruga, Małgorzata (Selected issues from the theory and practice of speech therapy, 2018)
Paper recalls importance of basic concepts related to oral cavity, which should be considered as a complete system of muscles and bones. There are discussed relations of muscle functions and structure of dental arches. Particular attention was concentrated on influence of the face muscles’ malfunctions on the shape of dental arches. It was emphasized that face proportions have crucial influence on the oral cavity organs. Especially stressed was importance of structure and function of muscles and dentoskeletal system on articulation of created.